2005
DOI: 10.1111/j.1471-4159.2005.03290.x
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell line‐derived neurotrophic factor‐induced signaling in Schwann cells

Abstract: Glial cell line-derived neurotrophic factor (GDNF), a known survival factor for neurons, has recently been shown to stimulate the migration of Schwann cells (SCs) and to enhance myelination. GDNF exerts its biological effects by activating the Ret tyrosine kinase in the presence of glycosylphosphatidylinositol-linked receptor, GDNF family receptor (GFR) a1. In Ret-negative cells, the alternative transmembrane coreceptor is the 140-kDa isoform of neural cell adhesion molecule (NCAM) associated with a non-recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 73 publications
(73 reference statements)
5
95
0
1
Order By: Relevance
“…We therefore tested the effects of Tyr 687 peptides on SHP2 activity. We found that the in vitro phosphatase activity of SHP2 recovered in immunoprecipitates from transfected COS cells was strongly enhanced by the addition of the phospho-Tyr 687 peptide but not by the corresponding non-phosphorylated peptide and could be blocked by the phosphatase inhibitor Na 3 VO 4 (Fig. 1C).…”
Section: Identification Of Shp2 As a Direct And Specific Interactor Omentioning
confidence: 86%
See 2 more Smart Citations
“…We therefore tested the effects of Tyr 687 peptides on SHP2 activity. We found that the in vitro phosphatase activity of SHP2 recovered in immunoprecipitates from transfected COS cells was strongly enhanced by the addition of the phospho-Tyr 687 peptide but not by the corresponding non-phosphorylated peptide and could be blocked by the phosphatase inhibitor Na 3 VO 4 (Fig. 1C).…”
Section: Identification Of Shp2 As a Direct And Specific Interactor Omentioning
confidence: 86%
“…Together with the neurotrophins, glial cell line-derived neurotrophic factor (GDNF) 4 and related family members are among the most important neurotrophic factors in mammals. Because of the potent prosurvival and neuroprotective effects of GDNF on midbrain dopaminergic neurons, much of the initial interest in GDNF was focused on its possible therapeutic effects in Parkinson disease (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the neurotrophic effects of GDF5 on DA neurons may be mediated indirectly through the action of glial cell line-derived neurotrophic factor (GDNF) (Sullivan and O'Keeffe 2005). To test this possibility, we adopted a similar approach to Orme et al (2013) who prevented the DA neurotrophic effects of GDNF by blocking its heparan sulphate-dependent signalling (Barnett et al 2002;Iwase et al 2005; Orme et al Supplementary Fig. 3).…”
Section: Bmpr Inhibitors Prevent Bmp2-and Gdf5-induced Neurite Outgromentioning
confidence: 99%
“…We noted pCREB was upregulated in SC nuclei following both the compressive and epineurotomy forms of ETS nerve repair. CREB phosphorylation may also occur downstream from NCAM-dependent autocrine GDNF-mediated signaling in SCs thus contributing to the SC proliferation observed in the compression and epineurotomy models (Iwase, et al 2005). pCREB was not colocalized to axons, but nuclear CREB phosphorylation secondary to long-range signaling through retrograde shuttling of receptor-ligand complexes was not evaluated (Riccio, et al 1997, Watson, et al 2001).…”
Section: Discussionmentioning
confidence: 99%